ASSOCIATION OF ETHNICITY AND CARCINOGEN WITH HEAD AND NECK CANCERS (The Research of Medical Science Review, 2025)
Objective: The purpose of this study is to review the complex relationship between the risk of head and neck cancer, exposure to carcinogens, and ethnicity. Study design: Cross sectional study Place and duration of study: This study is performed at ENT department of PNS Shifa hospital Karachi from January 2023 to July 2023 Methodology: A group of 220 patients who were presented at the outdoor department were selected after analyzing their eligibility on the basis of predefined criteria of inclusion and exclusion. All the patients with age between 18 to 85 years of either gender were included in this study. Results: The study included individuals with a mean age of 51.0 years (± SD 11.4), comprising 62.27% males and 37.73% females. The ethnic breakdown of biopsy- confirmed head and neck carcinoma cases revealed that 49.55% identifying as Urdu and varying percentages for Sindhi, Pashton, Balochi, Punjabi, and others. The carcinogen exposure data indicates significant usage of betel nuts (70.9%), gutka (65%), pan (79%), tobacco (83.6%), and naswar (74.09%) among participants, emphasizing the prevalence of various risk factors within the study population. Conclusion: This study has concluded that the incidence of head and neck of carcinomas has strong association with ethnicity and the exposure to various carcinogens like betel nut, tobacco, Naswar and gutka.